St Peter's, Barton-upon-Humber, Lincolnshire - A Parish Church and its Community: Volume 2 The Human Remains - Waldron, T. (Oxbow Books, 2007)
The excavations at St Peter's church, Barton-upon-Humber, between 1978 and 1984 have yielded the largest collection of human remains in the UK, dating from the late tenth century to the mid-nineteenth. The twin aims of the project were to understand the architectural history and setting of this complex, multi-period building (Volume 1), and to recover a substantial sample of the population for palaeopathological study (Volume 2). An extensive programme of historical and topographical research also took place in order to set the archaeological evidence firmly in context. Taking the long view over the entire period, however, it is striking how many of the marks of health and vigour, popularly supposed to have changed substantially between the middle ages and the Victorian era, have remained relatively constant. Together, the two volumes provide fascinating insights into that mainstay of settlement - the small English market town.
Description based on print version record.
KU Open Services
Keywords: Social Science / Archaeology; Social sciences; Electronic books